The possible threat of faking Covid-19 diagnostic tests and vaccination certifications: a call to an immediate action - Deguma, Melona C (J Public Health (Oxf), 2021)
The pandemic’s recessive effect on the global economy created a ‘de-globalized’ process that detrimentally causes financial turmoil to countries whose economy depends on tourism, urban passenger transport services and civil aviation, among others. The need to help the most vulnerable industries non-resilient to the pandemic reopen to aid economic recovery amid the pandemic’s threat is a very urgent concern. With the move to start the vaccination program against the threat of Covid-19, faking Covid-19 diagnostic testing certification pose a severe problem to matters of ethics and economics. If not taken seriously, falsifying documents that certify a person who has undergone Covid-19 vaccination could also happen. This paper argues that everyone’s collective effort could be the real embodiment of hope toward a new normal world immune from the virus and malpractices.